2017
DOI: 10.1212/nxi.0000000000000371
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune episodic ataxia in patients with anti-CASPR2 antibody-associated encephalitis

Abstract: Objective:To report paroxysmal episodes of cerebellar ataxia in a patient with anti–contactin-associated protein-like 2 (CASPR2) antibody-related autoimmune encephalitis and to search for similar paroxysmal ataxia in a cohort of patients with anti–CASPR2 antibody-associated autoimmune encephalitis.Methods:We report a patient with paroxysmal episodes of cerebellar ataxia observed during autoimmune encephalitis with anti-CASPR2 antibodies. In addition, clinical analysis was performed in a retrospective cohort of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 17 publications
1
43
0
1
Order By: Relevance
“… Neurological autoimmune disease Gene variant Alteration-Mechanism Reference Autoimmune ataxia CACNA1A Mutation in intron 39 (c5843-14G>A) play an essential role in calcium channels. [ 227 ] ITPR1 c.7721T>C(p.V2574A) Alteration in IP3 signaling by disrupting the calcium influx. [ 228 ] Autoimmune epilepsy LGI1 Modulation of Voltage-Gated Potassium Channel activity.…”
Section: Genetic Factorsmentioning
confidence: 99%
“… Neurological autoimmune disease Gene variant Alteration-Mechanism Reference Autoimmune ataxia CACNA1A Mutation in intron 39 (c5843-14G>A) play an essential role in calcium channels. [ 227 ] ITPR1 c.7721T>C(p.V2574A) Alteration in IP3 signaling by disrupting the calcium influx. [ 228 ] Autoimmune epilepsy LGI1 Modulation of Voltage-Gated Potassium Channel activity.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…Interestingly, a 64-year-old anti-Caspr2 Ab-positive man with paroxysmal episodes of CAs was reported [ 120 ]. He developed a paroxysmal episode of CAs one month after anti-Caspr2 Ab encephalitis.…”
Section: Clinical Autoimmune Background and Pathophysiological Actmentioning
confidence: 99%
“…He developed a paroxysmal episode of CAs one month after anti-Caspr2 Ab encephalitis. The authors retrospectively identified stereotyped episodes of paroxysmal CAs in five among 37 patients with anti-Caspr2 Ab-associated diseases [ 120 ]. The ataxic episodes, including gait imbalance (five patients), limb ataxia (three patients), slurred speech (three patients), and nystagmus (one patient), lasted a few minutes to a few days, and usually improved following immunotherapy (four patients), and sometimes spontaneously (one patient).…”
Section: Clinical Autoimmune Background and Pathophysiological Actmentioning
confidence: 99%
“…37 These antibodies can cause a broad range of neurological syndromes and are found in association with malignancy in approximately one-third of cases. CASPR2-associated ataxia can present as an episodic disorder, with initially reported attacks triggered by postural changes and/or emotions 38 both CASPR2 and GFAP antibody-positive patients respond to immunotherapy when caught early. Finally, NMDAR antibodies have also been described rarely with ataxia without other classic NMDAR encephalitis features.…”
Section: Cerebellar Ataxiamentioning
confidence: 99%